PEMBERIAN AIR REBUSAN BAWANG BOMBAY (Allium Cepa L) DALAM MEREGULASI KADAR GLUKOSA DARAH MENCIT DENGAN DIABETES MELITUS - Ariska Putri Hidayathillah; I Ketut Sudiana; Ika Yuni Widyawati (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: Diabetes mellitus is a degenerative disease with high prevalence that happens in many countries and high risk of causing death. The objective of this study is to know the effect of decoction by Allium cepa L on blood glucose level regulation in mice with diabetes mellitus.Method: This study was used a true experimental pre post test design with 30 samples, 8-12 weeks old-male mice, and 20-30 grams in weight. The mices were divided into five groups (normal control group, diabetes control group without treatment, treatment group with 3 gram/kg of decoction, treatment group with 4 gram/kg of decoction and treatment group with 5 gram/kg ofdecoction). The independent variable was Allium cepa L decoction (1cc) as a treatment, which is given per oral. Furthermore, the dependent variable was blood glucose level after 7 days treatment with Allium cepa L decoction.Result: The result showed that there were some differences between the treatment group and the diabetes control group without treatment for blood glucose level after giving treatment with Allium cepa L decoction (p<0.005). in other hand, there was no significant result between the normal group and the treatment group for blood glucose level after giving treatment with Allium cepa L decoction 5 gram/kg bb (p>0.005). Allium cepa L contains many substances which has many function to regulate blood glucose level.Discussion: It can be concluded that Allium cepa L decoction (5 gram/kg bb in 1 cc) is adequate for regulating blood glucose level in diabetes mellitus mice after 7 days treatment